Sustainable Procurement Practices and Organisational Performance of Small and Medium Enterprises in Ghana - Nangpiire, Clement; Gyebi, Francis Oheneba; Nasse, Theophile (International Journal of Economics and Financial Issues, 2024)
This study empirically examines the predictive relationship between sustainable procurement practices and its dimensions (staff competence, sustainable IT infrastructure and top management support) and the performance of Small and Medium Enterprises (SMEs). Using the explanatory research design, structured questionnaires were administered to 317 managers and owners of selected SMEs. The Structured equation modeling (SEM) via Smart PLS 4.0 was used for analyzing and testing the hypotheses. The findings show that top management support and sustainable IT infrastructure have moderately significant and positive impact on SMEs performance whilst staff competence did not have any statistically significant effect on SMEs performance. Even though staff competence did not have a statistically significant effect on SME performance in this context, managers and owners should not avoid training and developing staff competence as it may translate in affecting other aspects of business operation not accounted for by SME performance. Through the lens of the institutional theory, resource-based theory and the theory of altruism, the study proves the predictive relationship between sustainable procurement practices and small and medium enterprises in Ghana.